Reliability Based Task Allocation Scheme to Enhance the Performance of Distributed Environment - Khan, Faizul Navi; Govil, Kapil (International Journal of Computer Sciences and Engineering, 2014)
Distributed Environment (DE) aims at achieving higher execution speed than the one obtainable with uniprocessor system by exploiting the collaboration of multiple computing nodes interconnected in some fashion. The idea has been to partition a uniprocessor computing load into multiple units of execution and assigning them to the various processing nodes. The best possible speed up will obviously be obtained if the various partitions of the given computational task can run independently in parallel. The processing nodes of the system must be sharing the computational load of the system so as to be able to provide proper execution characteristics. All the processing nodes must be made busy as much as possible by receiving and executing multiple tasks. In such scenario the number of tasks are lesser than available number of processors in DE, the tasks will be assign to the processor without any concern, but incase the numbers of tasks are greater than the numbers of processors then the task allocation problem will introduce in to real life scenario. Task allocation problem for processing of ï¿½mï¿½ tasks to ï¿½nï¿½ processors (m>n) in a DE is presented here through a new modified tasks allocation scheme to allocate the task in DE. The allocation scheme, proposed in this paper allocates the tasks to the processor to increase the performance of the DE on the consideration of reliability of the task to the processors.